IBA-induced rooting in Nepenthes reinwardtiana Miq. cuttings for germplasm conservation - Ryan Budi Setiawan (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2025)
Nepenthes reinwardtiana Miq. is an endemic species distributed in Sumatra and Kalimantan and classified as least concern due to the lack of recent research data on its abundance and distribution. Excessive exploitation, deforestation, the long time required to reach the generative phase, and the dioecious flowering type have caused a population decline. Plant propagation through cuttings can support conservation activities. The success of cuttings is determined by the concentration of plant growth regulators (PGR), making studies on PGR concentration important. This research aimed to determine the best indole-3-butyric acid (IBA) concentration for inducing roots and shoots in N. reinwardtiana. The study was conducted from February to October 2023. The research was arranged based on a completely randomized design with IBA concentration treatments consisting of 5 levels: 0, 5, 10, 15, and 20 mg L-1. The results showed that there was no significant effect of IBA on all variables. However, 5 mg L-1 IBA gave the best responses on shoot height increase (10.9 cm), leaf number increase (5.0 leaves), and root length (8.7 cm). These findings suggest that the growth of N. reinwardtiana cuttings may rely heavily on endogenous auxin levels, reducing the observable effects of exogenous IBA application. The non-significant results highlight the potential of this species to thrive without external auxin under certain conditions, which could simplify propagation protocols. Keywords: biodiversity; conservation; endemic species; extinct; plant growth regulator